SELECTION OF BUFFALO MILK LACTIC ACID BACTERIA WITH PROBIOTIC POTENTIAL - Melia, Sri; Yuherman, Yuherman; Jaswandi, Jaswandi; Purwati, Endang (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this research was to isolate and identify lactic acid bacteria using 16S rRNA and evaluates their potential as probiotics. Methods: The probiotic properties measured were resistance to low pH and to 0.3% and 0.5% bile salts, antimicrobial activity against pathogenic bacteria (Escherichia coli O157:H7 and Staphylococcus aureus ATCC 25923), antibiotic resistance, and hydrophobicity. Results: The lactic acid bacteria with optimal probiotic properties were isolated from buffalo milk and identified from a sample from Agam district (BMA 3.3) which was classified using BLAST analysis as a strain of Lactobacillus fermentum (L23). Conclusion: Buffalo milk from this part of West Sumatera contains a strain of L. fermentum with has good probiotic properties.